1993
DOI: 10.1103/physrevc.47.473
|View full text |Cite
|
Sign up to set email alerts
|

Deuteron quadrupole moment and3S1

Abstract: Two values for the asymptotic D /S ratio of the deuteron g = 0.27 01+0.000 19 and g=0.02713+0.00006 are obtained using two empirical linear e, -Q and g-y Q relations we found for standard nonrelativistic potential models. It is shown that fitting the deuteron quadrupole moment Q, the deuteron rms matter radius rd, and the triplet scattering length a, simultaneously by a nonrelativistic nucleon-nucleon potential model is a critical task and it has been achieved by the inclusion of a shortrange attractive nonloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…8838+0.0004 fm '~o f Stoks et al [9] and the asymptotic D /S ratio g =0.0273+0.0005 of Borbely et al [10]. The value g = 0.0273+0.0005 of Borbely et al [10] is consistent, in particular, with our recent prediction g=0.02701+0.00019 [11]. The MHKZ potential fits too the experimental value of the deuteron quadrupole moment (Q = 0.2860+0.0015 fm [12] and Q =0.2859+0.0003 fm [13]).…”
supporting
confidence: 89%
“…8838+0.0004 fm '~o f Stoks et al [9] and the asymptotic D /S ratio g =0.0273+0.0005 of Borbely et al [10]. The value g = 0.0273+0.0005 of Borbely et al [10] is consistent, in particular, with our recent prediction g=0.02701+0.00019 [11]. The MHKZ potential fits too the experimental value of the deuteron quadrupole moment (Q = 0.2860+0.0015 fm [12] and Q =0.2859+0.0003 fm [13]).…”
supporting
confidence: 89%
“…In Refs. [23,43], a similar kinked feature was observed in the correlation function of neutral pions with nonperiodic implementations of a uniform electric field with the choice of a time-dependent gauge potential.…”
supporting
confidence: 59%
“…It was demonstrated that the deuteron quadrupole moment Q is approximately related to the asymptotic D/S ratio of the deuteron [4,5]. The theoretical results of Q and η almost lie on a straight line for the different most NN potentials.…”
Section: Introductionmentioning
confidence: 90%